一种制备异形微细通道板式换热器的复合工艺及系统 (2024)
本发明属于换热技术领域，公开了一种制备异形微细通道板式换热器的复合工艺及系统，基于激光选区熔融增材制造技术与微细电火花成型工艺形成的一种多种工艺相结合的复合工艺，实现了一种大纵横比流道以及封闭轮廓截面流道的异形微细通道板式换热器。使用本发明的复合工艺可以加工任意截面的通道，包括且不限于圆形、矩形等异形截面通道；可以加工中空封闭轮廓截面的流道,包括且不限于微细圆孔、微细方孔等异形截面通道；可以实现任意纵横比微细通道高精度加工，包括且不限于微细矩形等异形截面通道。使用本发明的复合工艺加工的换热器相较于一般的微细通道换热器可以耐受极端的高温高压工况，更加环保，无污染。 The present invention relates to the field of heat exchange technology, specifically to a composite process and system for producing a profiled microchannel plate heat exchanger. This process integrates selective laser melting additive manufacturing with micro electrical discharge machining to create microchannel plate heat exchangers featuring large aspect ratio flow channels and closed profile section flow channels. It enables the fabrication of channels with various cross-sections, such as circular and rectangular, as well as hollow closed profile section flow channels, including micro circular and square holes. The process allows for high-precision machining of microchannels with any aspect ratio. Heat exchangers produced usi